Super-stable non-woven fabric-based membrane as a high-efficiency oil/water separator in full pH range. Issue 32 (4th April 2017) - Diao, Zhongwei; Wang, Lei; Yu, Peng; Feng, He; Zhao, Li; Zhou, Wei; Fu, Honggang
Abstract : A polystyrene coated non-woven fabric hybrid membrane with superoleophilicity has been synthesized by a facile polymerization reaction for high-efficiency separation of oils in harsh environments. Abstract : Oil separation is very important for avoiding environmental pollution originating from industrial wastewater and oil spillage, and therefore it is essential to explore various materials for oil separation. Herein, a polystyrene-coated non-woven fabric (PS/non-woven fabric) hybrid membrane with superoleophilicity has been synthesized by a facile, green and low-cost in situ polymerization reaction. The oil separation kinetic mechanism of the hybrid membrane was also studied. The present hybrid membrane possesses advantages of flexibility and high efficiency, and demonstrates great potential applications in the various environments and even under different harsh conditions, which makes it very promising for the treatment of oil pollution in practical applications.